"if other arrangements can reasonably be made": the interior architecture of Children’s Courts in New Zealand in the 1930s - McCarthy, Christine (Architectural History Aotearoa, 2021)
In 1925, the Child Welfare Act was passed. The Act introduced the idea of the Children’s Court as a space "separate from the premises in which another Court usually exercises jurisdiction" (s28). In 1927, an amendment to the Act provided further elaboration, clarifying that: "persons attending any sittings of a Children’s Court shall not be brought into contact with persons in attendance at any other Court." To achieve this the amendment stipulated that: "for this purpose the sittings of the Children’s Court shall not, except in cases where no other suitable room is available, be held in any room in which any other Court ordinarily exercises jurisdiction; nor shall a sitting of the Children’s Court, if held in the same premises as any other Court, be held at a time when such other Court is sitting, if other arrangements can reasonably be made" (s18(1)). This paper investigates the locations, and interior architectures of Children’s Courts in New Zealand in the 1930s. It aims to establish whether or not the interior architecture of Children’s Courts, with their legislated requirement to be physically distinct from the rest of the court system, was also distinct, and in what ways children were specifically accommodated for in this interior architecture.